Revolutionizing medicine: Molecularly imprinted polymers as precision tools in cancer diagnosis and antibiotic detection: Molecularly imprinted polymers for medical diagnosis - Aminnezhad, Sargol; Hassan Aubais Aljelehawy, Qassim; Rezaei , Mohammad; Mohammadi, Mohammad Reza; Zonobian, Mohammad Ali; Nazari, Masomeh; Fathi, Fardin; Dadpour, Saba; Habibi, Paria; Kashanian, Soheila; Ashengroph, Morahem; Mohammadzade, Hadi; et al. (Cellular and Molecular Biology, 2024)
Molecularly imprinted polymers (MIPs) are pivotal in medicine, mimicking biological receptors with enhanced specificity and affinity. Comprising templates, functional monomers, and cross-linkers, MIPs form stable three-dimensional polymer networks. Synthetic templates like glycan and aptamers improve efficiency, guiding the molecular imprinting process. Cross-linking determines MIPs' morphology and mechanical stability, with printable hydrogels offering biocompatibility and customizable properties, mimicking native extracellular matrix (ECM) microenvironments. Their versatility finds applications in tissue engineering, soft robotics, regenerative medicine, and wastewater treatment. In cancer research, MIPs excel in both detection and therapy. MIP-based detection systems exhibit superior sensitivity and selectivity for cancer biomarkers. They target nucleic acids, proteins, and exosomes, providing stability, sensitivity, and adaptability. In therapy, MIPs offer solutions to challenges like multidrug resistance, excelling in drug delivery, photodynamic therapy, photothermal therapy, and biological activity regulation. In microbiology, MIPs serve as adsorbents in solid-phase extraction (SPE), efficiently separating and enriching antibiotics during sample preparation. They contribute to bacterial identification, selectively capturing specific strains or species. MIPs aid in detecting antibiotic residues using fluorescent nanostructures and developing sensors for sulfadiazine detection in food samples. In summary, MIPs play a pivotal role in advancing medical technologies with enhanced sensitivity, selectivity, and versatility. Applications range from biomarker detection to innovative cancer therapies, making MIPs indispensable for the accurate determination and monitoring of diverse biological and environmental samples.